2011
DOI: 10.1371/journal.pone.0015970
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Heparin Standardization: Combination of Scanning UV Spectroscopy, Nuclear Magnetic Resonance and Principal Component Analysis

Abstract: The year 2007 was marked by widespread adverse clinical responses to heparin use, leading to a global recall of potentially affected heparin batches in 2008. Several analytical methods have since been developed to detect impurities in heparin preparations; however, many are costly and dependent on instrumentation with only limited accessibility. A method based on a simple UV-scanning assay, combined with principal component analysis (PCA), was developed to detect impurities, such as glycosaminoglycans, other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 37 publications
(57 reference statements)
2
29
0
1
Order By: Relevance
“…Since DMMB dye reacts with all types of sulfated GAG chains, this assay was not able to distinguish the types of GAGs present in the mushroom extracts. Although our spectrophotometric analysis confirmed the presence of GAG chains at peaks around 190-210 nm (Lima et al, 2011), we also found additional broad peaks around 240-260 nm that were related to other aromatic compounds (de Micalizzi et al, 1998). Some ions, such as calcium or sodium, or the sulfation pattern of GAGs or other contaminants can shift the peaks (McEwen et al, 2009).…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Since DMMB dye reacts with all types of sulfated GAG chains, this assay was not able to distinguish the types of GAGs present in the mushroom extracts. Although our spectrophotometric analysis confirmed the presence of GAG chains at peaks around 190-210 nm (Lima et al, 2011), we also found additional broad peaks around 240-260 nm that were related to other aromatic compounds (de Micalizzi et al, 1998). Some ions, such as calcium or sodium, or the sulfation pattern of GAGs or other contaminants can shift the peaks (McEwen et al, 2009).…”
Section: Discussionmentioning
confidence: 47%
“…GAGs levels measured by the DMMB dye-binding assay from the top two mushroom extracts (log white fungi and bolete) were highly correlated with the highest absorption peak around 190-210 nm from spectrophotometric analysis; this tentatively represented the carboxylate chromophore of iduronate and glucuronate present in the GAGs chains (Lima et al, 2011), as shown in Figure 3 (L for log white fungi; and I for bolete). Although hygroscopic earthstar contained the highest levels of GAGs according to the DMMB dye-binding assay, its absorption (G) peak at around 190-210 nm was shifted toward the absorption peaks of the shitake mushroom (E), milk white russula (H), rosy russula (D), and sajor-caju mushroom (F) extracts.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Multivariate analysis was performed as previously described (Lima et al, 2011) using the software R: A Language and Environment for Statistical Computing (R Foundation for Statistical Computing, Viena, Austria. http://cran.r-project.org/), with prior mean centering.…”
Section: Multivariate Analysismentioning
confidence: 99%
“…Ennek az lehet az oka, hogy a természetes eredetű, marha légcsőből előállított CSA a kinyerési eljárás következtében szennyezésként cetil-piridínium-kloridot (CPC) tartalmaz (Garnjanagoonchorn et al, 2007;Lima et al, 2011), és ez adszorbeálódva a magnetit részecskéken azok egy részét hidrofobizálja, destabilizálja. UV méréssel tudtam igazolni a szennyező jelenlétét, ugyanis a CPC-nak jellemző elnyelése van 260 nm-nél (Lima et al, 2011;Roach et al, 2013;Song et al, 2007). Ez a csúcs megjelent a CSA oldatában mért UV spektrumon, azonban az adszorpció után az egyensúlyi felülúszó már nem tartalmazta ezt a csúcsot, még nagy feleslegben alkalmazott CSA esetében sem.…”
Section: A Polielektrolitok Adszorpciós Izotermái Magnetit Nanorészecunclassified